Implementation of Sustainable Finance and Environment - Winona Bianda Callista; Choirul Anwar; Hafifah Nasution (Journal Research of Social Science, Economics, and Management, 2021)
This study aims to determine management's perception of strategy in implementing sustainable finance and environment in related companies. This study uses primary data with phenomenological research methods obtained through interviews, documentation, and analysis of the content of sustainability reports to obtain more detailed information. The subject of this research is the management of a construction company in Indonesia. The result of this research is the implementation to achieve sustainable finance is by budgeting for investment by considering environmental, social, and governance factors. Implementation of sustainable finance as a component of green finance that aims to support balanced economic growth. The implementation of a sustainable environment along with the company's social aspects is summarized in the K3L (Health, Occupational Safety, and Environment) policy.